Peranan Prinsip Good Governance pada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu (DPM-PTSP) Kabupaten Wajo - Jamal Qadar; Burhanuddin Burhanuddin; Yuniarni Yuniarni (Parlementer : Jurnal Studi Hukum dan Administrasi Publik, 2024)
This study aims to determine the application of good governance principles at the Wajo Regency Investment and One-Stop Integrated Services Office (DPM-PTSP), the research informants consist of staff and employees along with the public who want to take care of licensing letters at the Wajo Regency DPM-PTSP Office. This study uses a qualitative method with a descriptive approach.The results of this study show that the application of Good Governance principles at the Wajo Regency Investment and One-Stop Integrated Services Office (DPM-PTSP) has been running well, including accountability that has been effective and efficient in terms of achieving strategic objectives that contain vision, mission, goals and objectives, and activities that are equipped with performance indicators and targets to be achieved, Transparency with the accountability of staff and employees in carrying out their respective duties which are quite professional, Participation shows that the community feels very satisfied with public services, and the Rule of Law is also very good because it is carried out fairly without discriminating against the social status of the community. The conclusion is that the application of the Good Governance Principle at the Wajo Regency DPM-PTSP office has been realized and implemented well.